Application of Data Mining Techniques on Software Engineering Data for Software Quality (International Journal of Engineering and Computer Science, 2014)
The processes of Software engineering are complex and produces large number and variety of artifacts. The potential of data mining technique on this large valuable data is  to better manage the software projects and to produce high-quality software systems that are delivered on time and within budget.  This paper present the latest research in mining software engineering data, software engineering task helped by data mining, kind of software engineering data, data mining techniques used in software engineering.